Social Contracts for Development : Bargaining, Contention, and Social Inclusion in Sub-Saharan Africa - Cloutier, Mathieu (Washington, DC: World Bank and Paris: Agence française de développement, 2021)
Sub-Saharan Africa has achieved significant gains in reducing the levels of extreme poverty in recent decades, yet the region continues to experience challenges across the development indicators, including energy access, literacy, delivery of services and goods, and jobs skills, as well as low levels of foreign direct investment. Exacerbating the difficulties faced by many countries are the sequelae of conflict, such as internal displacement and refugee migration. Social Contracts for Development: Bargaining, Contention, and Social Inclusion in Sub-Saharan Africa builds on recent World Bank attention to the real-life social and political economy factors that underlie the power dynamic and determine the selection and implementation of policies. Applying a social contract approach to development policy, the authors provide a framework and proposals on how to measure such a framework to strengthen policy and operational engagements in the region. The key message is that Africa’s progress toward shared prosperity requires looking beyond technical policies to understand how the power dynamics and citizen-state relations shape the menu of implementable reforms. A social contract lens can help diagnose constraints, explain outbreaks of unrest, and identify opportunities for improving outcomes. Social contract assessments can leverage the research on the nexus of politics, power relations, and development outcomes, while bringing into focus the instruments that underpin state-society relations and foster citizen voice. Social contracts also speak directly to many contemporary development trends, such as the policy-implementation gap, the diagnostic of binding constraints to development, fragility and conflict, taxation and service delivery, and social protection. The authors argue that policies that reflect the demands and expectations of the people lead to more stable and equitable outcomes than those that do not. Their focus is on how social contracts are forged in the region, how they change and why, and how a better understanding of social contracts can inform reform efforts. The analysis includes the additional impact of the COVID-19 (coronavirus) pandemic on government-citizen relationships.